Relación entre la caries dental y el índice de masa corporal en niños de preescolar: una revisión sistemática (2021)
Dental caries is a multifactorial chronic disease that affects children in their primary dentition; its etiology is multifactorial and is associated with biological, behavioral and sociodemographic determinants; among these malnutrition and obesity linked to poor nutrition, this relationship can be represented from BMI.